2013
DOI: 10.1371/journal.pone.0059554
|View full text |Cite
|
Sign up to set email alerts
|

Prion Protein Is Decreased in Alzheimer's Brain and Inversely Correlates with BACE1 Activity, Amyloid-β Levels and Braak Stage

Abstract: The cellular prion protein (PrPC) has been implicated in the development of Alzheimer's disease (AD). PrPC decreases amyloid-β (Aβ) production, which is involved in AD pathogenesis, by inhibiting β-secretase (BACE1) activity. Contactin 5 (CNTN5) has also been implicated in the development of AD by a genome-wide association study. Here we measured PrPC and CNTN5 in frontal cortex samples from 24 sporadic AD and 24 age-matched control brains and correlated the expression of these proteins with markers of AD. PrP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 41 publications
3
29
2
Order By: Relevance
“…Whitehouse et al measured PrP C in the frontal cortex of 24 sporadic AD brains vs. 24 age-matched controls and found a significant decreased of PrP C in AD brains. Interestingly, PrP C significantly inversely correlated with BACE1 activity, Aβ load, soluble Aβ, and insoluble Aβ and with the stage of disease, as indicated by Braak tangle stage (Whitehouse et al, 2013). The authors concluded that brain PrP C level may be important in influencing the onset and progression of sporadic AD (Whitehouse et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whitehouse et al measured PrP C in the frontal cortex of 24 sporadic AD brains vs. 24 age-matched controls and found a significant decreased of PrP C in AD brains. Interestingly, PrP C significantly inversely correlated with BACE1 activity, Aβ load, soluble Aβ, and insoluble Aβ and with the stage of disease, as indicated by Braak tangle stage (Whitehouse et al, 2013). The authors concluded that brain PrP C level may be important in influencing the onset and progression of sporadic AD (Whitehouse et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest to us are the controversial issues in the literature linking Aβ oligomers and PrP C (Laurén et al, 2009; Nygaard and Strittmatter, 2009; Gunther and Striitmatter, 2010; Kessels et al, 2010; Barry et al, 2011; Saijo et al, 2011; Larson et al, 2012; Um et al, 2012; Chen et al, 2013; Kudo et al, 2013; Whitehouse et al, 2013; Younan et al, 2013). A few specific examples to make the point: Kudo et al showed that Prnp (-/-) mice are resistant to the neurotoxic effect of oligomeric Aβ in vivo and in vitro (Kudo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Aβ accumulates during pathogenesis of Alzheimer's disease (AD) and PrP C reportedly acts as an inhibitor of β-secretase 1 (Parkin et al, 2007; Whitehouse et al, 2013), thereby reducing the amount of Aβ produced and suggesting that PrP C expression should protect against the development of AD. A feedback loop has also been proposed that consists of the APP intracellular domain (the other fragment produced by cleavage of sAPPβ) activating cellular tumour antigen p53, which subsequently upregulates PrP C expression, leading to further inhibition of β-secretase 1 activity (Vincent et al, 2009).…”
Section: Prpc Functionmentioning
confidence: 99%
“…Authors of this study point out that a decreased level of PrP c results in a decreased zinc uptake within the synapses. Such condition results in an elevated synaptic zinc level, which favours binding Aβ oligomers to the NMDA receptors, and mediates the excitotoxicity [86]. In our opinion, it is more probable that an inverse correlation with Braak stage assessed tauopathy was caused by the elevation of Aβ and PrP c ratio, and its direct impact on tau expression.…”
Section: Cooperation?mentioning
confidence: 86%